OVERVIEW OF STEM CELL THERAPY (World Bulletin of Public Health, 2022)
Stem cells are a distinct and versatile type of cell that can divide endlessly and have a special ability to regenerate. Additionally, it was capable of differentiating into various cell types and growing into adult cells with specialized functions and distinguishing features, like heart or skin cells (Wakitani et al., 1995), ligament (Altman et al., 2002), adipose tissue (Beresford et al., 1992), muscle, nerve cells ,cartilage (Johnstone et al., 1998; Yoo et al., 1998) . A stem cell is uncommitted and remained uncommitted until it received a signal to develop into a specialized cell.
Keywords: Stem; muscle; nerve cells